932 Delivering Excellence in Orthopaedic Training - A Five Year Qualitative Study of Characteristics Valued by Trainees Voting for Trainer of The Year. (12th October 2021) - Ali, R; Wharton, R; Li, L; Waterman, J
Abstract: Background: Previous studies have described attributes of successful trainers. Dean et al's (2017) systematic analysis found 12 commonly cited positive characteristics in medical literature. This paper and Nisar et al's (2011) study which had a more exhaustive list of desirable qualities in surgical trainers formed the basis of our thematic analysis to identify trainer characteristics/behaviours valued by trainees on an orthopaedic training programme. Method: We evaluated qualitative data from votes on the North West Thames rotation for Trainer of the Year over a 5-year period (2016-2020). We applied thematic analysis to identify 15 characteristics commonly cited by trainees in their nominations and logged how frequently each characteristic was raised. Results: The five most popular qualities possessed by nominees are 1) prioritisation of training needs and endeavouring to create more training opportunities for trainees 2) being a source of support 3) willingness to allow trainees to operate 4) setting and facilitating the achievement of educational goals/targets 5) providing appropriate levels of supervision. All 15 valued characteristics and their frequency of mention are listed in the table presented. Conclusions: To the best of our knowledge this is the only study which focuses exclusively on desirable qualities orthopaedic specialist trainees' value in their trainers. 'Advocating for trainees' is a valued quality, also highlighted in ASIT's 2018 analysis of the Silver Scalpel Award nominations, which is not otherwise well described in the literature. We hope our work will allow aspiring orthopaedic trainers insight into what trainee's value most in a surgical mentor.